2011
DOI: 10.1152/physiolgenomics.00080.2011
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes for panhypopituitarism identified by gene expression profiling

Abstract: Mutations in the transcription factors PROP1 and PIT1 (POU1F1) lead to pituitary hormone deficiency and hypopituitarism in mice and humans. The dysmorphology of developing Prop1 mutant pituitaries readily distinguishes them from those of Pit1 mutants and normal mice. This and other features suggest that Prop1 controls the expression of genes besides Pit1 that are important for pituitary cell migration, survival, and differentiation. To identify genes involved in these processes we used microarray analysis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 93 publications
2
20
0
Order By: Relevance
“…As expected, Otx2 mRNA was detected in both the retina and pineal. Interestingly, and as expected from recent data of the literature (see Introduction and Mortensen et al [41]), Otx2 mRNA was also expressed in the pituitary.…”
Section: Resultssupporting
confidence: 87%
“…As expected, Otx2 mRNA was detected in both the retina and pineal. Interestingly, and as expected from recent data of the literature (see Introduction and Mortensen et al [41]), Otx2 mRNA was also expressed in the pituitary.…”
Section: Resultssupporting
confidence: 87%
“…FACS-sorted E-cadherinand E-cadherin + cells were defined as hypothalamus and oral ectoderm cells, respectively. (B) Quantitative RT-PCR of OTX2 in FACS-sorted hypothalamus and oral ectoderm (day [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. OTX2 expression was higher in hypothalamus than in oral ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…OTX2 protein binds to the promoters of HESX1 and POU1F1, which are expressed in oral ectoderm and required for pituitary development, and directly upregulates their expression (11,12,14), suggesting the role of OTX2 expressed in the oral ectoderm. On the other hand, it has been shown that not oral ectoderm-specific but hypothalamus-specific Otx2-deficient mice exhibited impaired anterior pituitary development, suggesting that the OTX2 expressed in the hypothalamus plays an important role in pituitary development (15,16); however, the precise underlying mechanisms, especially in humans, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Otx1 -/- mutants have an even milder phenotype, resulting in a transient delay in growth and puberty 92 , supporting the idea that both Otx1 and Otx2 have roles in pituitary development, with Otx2 being the most critical for normal organ morphology and function. Otx2 is prominently expressed in the neural ectoderm, which produces FGF and stimulates the growth of Rathke’s pouch 79 . Otx2 expression in Rathke’s pouch is very low and transient, and little or no expression is apparent when Pou1f1 transcription is initiated.…”
Section: Early Acting Transcription Factorsmentioning
confidence: 99%